Literature Review Paper on Mechanical Properties of Types of Carbon Nanotubes - Randjbaran Elias; Zahari; Laila Abang Haji Abdul Majid Dayang; Thariq Bin Hameed Sultan Mohamed; Mazlan Norkhairunnisa (Journal of New Developments in Chemistry, 2018)
Among the numerous potential uses of carbon nanotubes (CNT), its utilization to fortify polymers was given careful consideration. This reason can be because of the remarkable firmness, magnificent quality, and the low thickness of CNT. This has given various chances to the innovation of new material frameworks for applications requiring high quality and high modulus. Exact control over preparing factors, including safeguarding flawless CNT structure, uniform scattering of CNT inside the polymer grid, compelling filler– lattice interfacial communications, and arrangement/introduction of polymer chains/CNT, add to the composite strands' unrivalled properties. Consequently, manufacture techniques assume an imperative part in deciding the composite filaments' microstructure and extreme mechanical conduct. The present best in the class of polymer/CNT elite composite filaments, particularly concerning processing– structure– execution, were looked into in this commitment. Future requirements for material by configuration approaches for handling these nano-composite frameworks were likewise examined.
Keywords: carbon nanotubes